A new combination in Leucopholiota (Agaricales, Fungi) - Harmaja, Harri (Phytotaxa, 2013)
Leucopholiota lignicola (P.Karst.) Harmaja, comb. nov. Basionym:—Lepiota lignicola Karsten (1879: 547) Type:—Finland, Etelä-Häme, Tammela, September 1879, P.A. Karsten s.n., Herbarium Karsten no. 2034 (holotype H!). Synonym:—Amylolepiota lignicola (P.Karst.) Harmaja (2002: 40). The new monotypic genus Amylolepiota Harmaja (2002: 39) was established to accommodate Lepiota lignicola that was deviating in Lepiota especially through the amyloid spore wall. I have now reconsidered the taxonomic position of that species, and regard it as belonging to the closely related, likewise originally monotypic genus Leucopholiota (Romagn.) Miller, Volk & Bessette (1996: 138), with Agaricus decorosus Peck (1873: 73) as the type. Knudsen (2008) indicated both generic and specific synonymy of Amylolepiota lignicola with Leucopholiota decorosa (Peck) Miller, Volk & Bessette (1996: 138).